2012
DOI: 10.1155/2013/314790
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Preparation of Activated Carbon from Ricinus communis Leaves by Microwave‐Assisted Zinc Chloride Chemical Activation: Competitive Adsorption of Ni2+ Ions from Aqueous Solution

Abstract: The preparation of activated carbon (AC) fromRicinus communisleaves was investigated in this paper. Orthogonal array experimental design method was used to optimize the preparation of AC using microwave assisted zinc chloride. Optimized parameters were radiation power of 100 W, radiation time of 8 min, concentration of zinc chloride of 30% by volume, and impregnation time of 24 h, respectively. The surface characteristics of the AC prepared under optimized conditions were examined by pHZPC, SEM-EDAX, XRD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…The isotherm represents the specific relation between the concentration of adsorbate and its degree to accumulation onto adsorbent surface at constant temperature [20]. This supports the theory that the number of active sites on the both carbon surface is limited and methylene blue forms a monolayer on the surface [25]. Langmuir constant q m and adsorption capacity log K were determined from the slope and intercept of the plot are presented (Table: 2).…”
Section: Adsorption Isothermsupporting
confidence: 65%
“…The isotherm represents the specific relation between the concentration of adsorbate and its degree to accumulation onto adsorbent surface at constant temperature [20]. This supports the theory that the number of active sites on the both carbon surface is limited and methylene blue forms a monolayer on the surface [25]. Langmuir constant q m and adsorption capacity log K were determined from the slope and intercept of the plot are presented (Table: 2).…”
Section: Adsorption Isothermsupporting
confidence: 65%
“…The experiments were done in 250-mL flasks each containing 50 ml of different initial pHÁNaNO 3 solutions, and 0.2 g of adsorbent ANZ was added. The pH values were adjusted using 0.1 M HCl and 0.1 M NaOH (Makeswari and Santhi 2013). After stabilization, the final pH was recorded.…”
Section: Zero Point Chargementioning
confidence: 99%
“…It has been reported that the grater the atomic weight, electronegativity, electrode potential and ionic size, the grater will be the affinity for sorption. It is clear that the electronegativity is a dominant factor for adsorption (Makeswari and Santhi 2013).…”
Section: Effect Of Cu(ii) Ions and Cr(vi) Ions On Adsorption Of Ni(iimentioning
confidence: 99%
“…This means that the adsorption is highly dependent on the initial concentration of Chromium ion. This is because the ratio between the surface available on the adsorbent and the concentration of metal ion in the solution phase decrease with the increase of initial concentration of the solute [12]. The results obtained from pseudo first order and second order kinetic models for Chromium (VI) ions were presented in Table 3.Concerned graphs at 305 K were shown in Figures 5 and 6.…”
Section: Effect Of Dosementioning
confidence: 99%